ANALYSIS OF COMPLIANCE FACTORS FOR HEALTH PROTOCOL OF DENTISTS AT PEKANBARU HEALTH CENTERS DURING COVID-19 - Alfionita, Indri; Niam, Moh Husnun; Ardlina, Nira (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Coronavirus disease is a respiratory disease caused by SARSCoV2, a new type of virus. COVID-19 infection can occur during dental surgery and possibly inhalation of aerosols or droplets containing the virus. One element of the success of health institutions is the compliance of health workers in carrying out health procedures during a pandemic. The large number of COVID-19 cases at Indonesian dentists requires the implementation of Health Guidelines in health care institutions. This study aims to determine the effect of the health protocol compliance factor of the Puskesmas dentists in Pekanbaru City during the COVID-19 outbreak.Method: This study used an analytic observational approach, quantitative research methodology, and a cross-sectional design on 21 dentists who work actively in public health centers in Pekanbaru City. The data analysis technique used univariate and bivariate analysis using Alternative Fisher's Exact Test.Result: The results showed there is a difference between the availability of infrastructure for compliance was statistically tested on two factors with a p value of less than 0.05 (P=0.048.) as many as 95.2% of dentists comply with health regulations.Conclusion: The conclusion of the study There was a relationship between the availability of facilities and infrastructure and the dentist's compliance with health procedures at the puskesmas in Pekanbaru City during the pandemic.